Kaiser Community Homes in Santa Clara and San Jose, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Image showing homes of the Kaiser Community Homes real estate development on Newhall Street at Park Avenue in Santa Clara and San Jose, California.